Antecedents of Implementing e-HRM Practices: Key Drivers and Influences - Suba D, Chandrasekar, Arockiam Kulandai (Journal of Informatics Education and Research, 2025)
This conceptual paper aims to investigate how effective electronic Human Resource practices are applied in corporates to strengthen employee performance by saving employees’ time through high-quality HR services. Today, electronic applications and tools are widely utilized in HRM practices for onboarding, training, performance management, communication, compensation, and employee engagement. These tools reduce the time required to deliver quality HR services, which helps minimize employee dissatisfaction, streamline HR processes, mitigate conflicts between management and employees, and ultimately guide employees toward increased productivity. In contrast, conventional HR practices often led employees to spend time resolving issues related to compensation, training, and performance management. For this research, the author examined 59 articles from prominent publishers, including Sage, Taylor & Francis, Elsevier, Springer, Emerald, and ResearchGate. The researchers conducted a meta-analysis in accordance with the PRISMA guidelines and found that e-HRM practices have a significant correlation with employee productivity, primarily due to the provision of high-quality HR services.